THE QUALITY EVALUATION OF SMOKE FLAVORED CATFISH (Cryptopterus bicirchis) COMPARED TO TRADITIONALLY SMOKED FISH DURING STORAGE - Afrinaldi Hamdi; Edison '; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research aimed to compare the quality of smoke flavored to the traditionally smokedcatfish smoked catfish (Cryptopterus bicirchis). The research was using experimental methodand composed as a randomized block design. There were two smoking methods, those weretraditionally hot smoking and liquid smoking. The liquid smoke used for soaking the fish wasvaried to crude liquid smoke and redistilled liquid smoke. The quality of the smoked fishproducts were evaluated for the value of sensory, water content, value of pH, content of totalacid, content of total phenol, and TPC. The result showed that the quality of all smoke catfishproduct could be stored for 30 days at room temperature. At the first day before storage, thevalue of the appearance was 8,8, the value of the odor was 8,7, the value of the flavor was 8,8,and the value of the texture was 8,8. The chemical characteristic showed that the content ofmoisture was 14.38 %, the pH value was 6.7, content of the total acids was 3.75%, content of thetotal phenols was 0.97 ppm, and the TPC was 3.65 cfu/g. However, up to the end of the storage,the ptoduct of traditionally smoked catfish was indicating the highest quality, showed by thehighest sensory value of the product at the end of storage. The value of the appearance was 6,8(the surface appearance was intact, tidy, the color was getting dim), the value of the odor was 7,1(the specific smell of smoke started dwindling and bad odor compounds started to smell), thevalue of the flavor was 6,6 (the savory flavor and the specific flavor started dwindling, bad flavorcompounds started to taste), and the value of the texture was 6,8 (the texture started fragile andsomewhat moist).Key Word : crude liquid smoke, Cryptopterus bicirchis, hot smoking, liquid smoking, redistilledliquid smoke